독활기생탕과 가미사육탕 가감방의 요통, 슬관절통 호전도에 대한 임상적 고찰 - 최찬헌; Chan Hern Choi; 김선종; Sun Jong Kim; 신정철; Jeong Cheol Shin; 위통순; Tong Soon Wi; 김재홍; Jae Hong Kim; 최진봉; Jin Bong Choi; et al. (大韓本草學會誌, 2013)
Objective: This study was to evaluate the effectiveness of the prescription Dokhwalkigisaengtangagambang(DGG) and Gamisayuktanggagambang(GSG), which has been utilized in the treatment of joint disease, for improving low back and knee joint pain. Methods: In the patients for the clinical studies, control group was 28 cases, experimental group was 41 cases. All subjects had low back pain and knee pain. The experimental group was treated with DGG or GSG, the control group was treated with 17 prescriptions. VAS (Visual Analag Scale), WOMAC (Western Ontario and McMasters Universties Osteoarthritis Index) and ODI (Oswestry Low back pain Disability index) measured before and after the prescription administration. Results : In the difference of VAS score, the experimental group (p <0.001) and the control group (p <0.001) were decreased significantly before and after the administration of prescription, and in the comparisons between the experimental group and the control group, experimental group was decreased significantly compared to the control group(p = 0.008). In the WOMAC score, there was no significant difference between the experimental group and the control group. In the difference of ODI items score, lifting (p = 0.020) and sleeping (p = 0.028) index were decreased significantly before and after the administration of prescription. Conclusion: The results indicated that the prescription DGG and GSG can reduce knee pain and low back pain. This study will be helpful for improving joint disease.